2016
DOI: 10.22270/jddt.v6i6.1238
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Potentially Inappropriate Medications in Ayder Referral Hospital, Tigray Region, Northern Ethiopia: Prospective Study

Abstract: Background: Potentially inappropriate medication (PIM) use includes the use of drugs with higher risk where adverse drug effect outweighs the clinical benefit, especially when more effective alternative therapy is available. Objective: The aim of this study was to assess prevalence and risk factors associated with the use of PIMs in elderly patients at medical ward of Ayder Referral Hospital (ARH), Tigray region, Northern Ethiopia. Methods: A facility based prospective cross sectional study was conducted among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 10 publications
3
28
2
Order By: Relevance
“…This study sought to assess the prevalence and determinants of multimorbidity, polypharmacy, and PIM use among older patients attending chronic care clinics in Ethiopia. Overall, the prevalence of multimorbidity and PIM use is becoming increasingly common in Ethiopia, and our findings are in concordance with other studies [ 18 , 19 , 20 , 23 , 24 ]. It was found that around 60% of the older adults had multimorbidity, a quarter of them experienced polypharmacy, and nearly half (47.1%) of them were being treated with at least one PIM during the study period.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study sought to assess the prevalence and determinants of multimorbidity, polypharmacy, and PIM use among older patients attending chronic care clinics in Ethiopia. Overall, the prevalence of multimorbidity and PIM use is becoming increasingly common in Ethiopia, and our findings are in concordance with other studies [ 18 , 19 , 20 , 23 , 24 ]. It was found that around 60% of the older adults had multimorbidity, a quarter of them experienced polypharmacy, and nearly half (47.1%) of them were being treated with at least one PIM during the study period.…”
Section: Discussionsupporting
confidence: 93%
“…The United Nations (UN) estimated that individuals aged 65 years and older accounted for 3.6% of the Ethiopian population in 2020 and is expected to reach 5.2% by 2050 [ 15 ]. Previous studies have investigated the extent of polypharmacy and PIM use using START/STOPP criteria and Beers criteria [ 16 , 17 , 18 , 19 , 20 , 21 ] and found poor medication-related quality of life among Ethiopian older patients [ 22 ]. Moreover, a recent meta-analysis from Ethiopia reported a high prevalence of PIM use (37%) among the older population [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Middle East, several studies have reported a high prevalence of PIMU; 57.5% from Saudi Arabia [ 14 ], 62.6 and 76.0% from Qatar [ 15 , 16 ], 59.6% from Lebanon [ 17 ], and 53.1% from Kuwait [ 18 ]. In Africa, one study from Nigeria [ 19 ] reported a 31% PIMU among older adult patients, while studies from Ethiopia revealed a nearly similar magnitude of PIMU; 27.72% from Gondar [ 20 ], 23% from Dessie [ 21 ], and 28.6% from Tigray [ 22 ]. Using STOPP/START, a study from Kuwait [ 18 ] reported at least one PIMU in 55.7%, while in a study from Gondar [ 23 ] PIMU was identified in 61.5% of older adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…In Middle East, several studies have reported a high prevalence of PIMU; 57.5% from Saudi Arabia (14), 62.6% and 76.0% Qatar (15,16), 59.6% from Lebanon (17), and 53.1% from Kuwait (18). In Africa, one study from Nigeria (19) reported a 31% PIMU among elderly patients, while studies from Ethiopia revealed nearly similar magnitude of PIMU; 27.72% from Gondar (20), 23% from Dessie (21), and 28.6% from Tigray (22). Using STOPP/START, a study from Kuwait (18) reported at least one PIMU in 55.7%, while in a study from Gondar (23) PIMU was identi ed in 61.5% in of elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, studies are limited. One study from Nigeria (19) reported a 31% of PIMU, while in Ethiopia, studies from Tigray(22); Gondar(20), and Dessie(21) reported PIMU in 28.6% 27.7%, and 23% of the elderly patients, respectively. The discrepancy in the magnitude of PIMU could be due to many factors.…”
mentioning
confidence: 99%